Analisis Karakter Klinikopatologik pada Kasus Karsinoma Payudara Subtipe Luminal A Like - Susanto, Andi; Dewayani,, Birgitta Maria; Hernowo, Bethy Surjawathy (Majalah Patologi Indonesia, 2021)
BackgroundMolecular subtypes of breast carcinoma, luminal A like has the best prognosis, but in the previous studies there were cases thatshowed poor clinical outcomes. This study attempted to investigate the clinicopathological characteristics in luminal A like subtypebreast carcinoma.MethodsThis study is a cross sectional study. The samples used were 67 medical records of patients with luminal A like subtype breastcarcinoma in January 2014 to June 2019 period from Hasan Sadikin Hospital, Bandung. According to estrogen receptor (ER) andprogesteron receptor (PR) expression status by adding both intensity and distribution scores, the data were divided into twosubgroups: low histoscore (<7) and high histoscore (â‰¥7). Clinicopathological characteristics (age, TNM stage, treatment, location,histologic type, grading and metastasis) were evaluated for each subgroup.ResultsFrom 67 luminal A like subtype breast carcinoma patients, 73.13% were in the high histoscore subgroup, with higher percentage oflow grade histopathologic features (63.27%). There were no significant differences in age and TNM staging between the twosubgroups. Among 67 breast carcinoma patients, 43 were diagnosed in advanced stages. There were significant differences inlymph nodes metastasis between the two subgroups (p-value 0.013), however, there were no significant difference in metastasis toother organs.ConclusionThis study shows that 73.13% of patients with luminal A like subtype breast carcinoma have a high histoscore of hormone receptor.Low histoscore subgroups luminal A like subtype breast carcinoma will metastasize to lymph nodes.